The Collapsible Soil, Types, Mechanism, and identification: A Review Study (Journal of Engineering, 2022)
Collapsible soil has a metastable structure that experiences a large reduction in volume or collapse when wetting. The characteristics of collapsible soil contribute to different problems for infrastructures constructed on its such as cracks and excessive settlement found in buildings, railways channels, bridges, and roads. This paper aims to provide an art review on collapse soil behavior all over the world, type of collapse soil, identification of collapse potential, and factors that affect collapsibility soil. As urban grow in several parts of the world, the collapsible soil will have more get to the water. As a result, there will be an increase in the number of wetting collapse problems, so it's very important to comprehend these soils' collapse mechanisms under different conditions such as reduction in capillary rise force upon wetting, the concentration of the soluble salts, deficiency of clays and under compaction that attributed the collapse potential to the nature of character of the porous fabric of loess soil.